2012
DOI: 10.1128/jvi.00598-12
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Human Cytomegalovirus Reactivation Is Maturation Dependent in the Langerhans Dendritic Cell Lineage and Can Be Studied using a CD14+Experimental Latency Model

Abstract: Studies from a number of laboratories have shown that the myeloid lineage is prominent in human cytomegalovirus (HCMV) latency, reactivation, dissemination, and pathogenesis. Existing as a latent infection in CD34؉ progenitors and circulating CD14 ؉ monocytes, reactivation is observed upon differentiation to mature macrophage or dendritic cell (DC) phenotypes. Langerhans' cells (LCs) are a subset of periphery resident DCs that represent a DC population likely to encounter HCMV early during primary infection. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
60
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 66 publications
(92 reference statements)
5
60
0
Order By: Relevance
“…1B). This phenotype was consistent with a more immature dermal, and not Langerhans, DC phenotype (25), similar to that observed for classical MoDCs (20,25), which have been used routinely to study HCMV latency and reactivation. Taken together, these data suggested that the circulating blood DCs isolated were predominantly of a dermal/interstitial-like phenotype, consistent with previous reports for the isolation of myeloid blood DCs from healthy donors (40,41).…”
Section: Dendritic Cells Directly Isolated From Peripheral Blood Are supporting
confidence: 51%
See 3 more Smart Citations
“…1B). This phenotype was consistent with a more immature dermal, and not Langerhans, DC phenotype (25), similar to that observed for classical MoDCs (20,25), which have been used routinely to study HCMV latency and reactivation. Taken together, these data suggested that the circulating blood DCs isolated were predominantly of a dermal/interstitial-like phenotype, consistent with previous reports for the isolation of myeloid blood DCs from healthy donors (40,41).…”
Section: Dendritic Cells Directly Isolated From Peripheral Blood Are supporting
confidence: 51%
“…However, crucially, while a wealth of in vitro data supports this prevailing hypothesis, it has never been definitively shown that naturally occurring DCs derived from healthy seropositive individuals are sites of genome carriage and, importantly, sites of HCMV reactivation. Indeed, a previous study of CD11c ϩ dendritic cells isolated from buffy coats of healthy volunteers has suggested that the welldocumented immunoparalysis observed following infection of in vitro-differentiated DCs (20,(30)(31)(32)(33)(34)(35)(36)(37) is not observed when circulating DCs are similarly infected in vitro with HCMV (38). Although these data concern lytic infection, they exemplify the need for a direct analysis of HCMV latency and reactivation in DCs.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…CMV-infected DCs displayed abnormal phenotypic characteristic and stable expression of CD83 as a maturation marker [24,25] . Infectivity of CMV in MoDCs resulted in maturation of the surviving cells, upregulation of the CD86, and down-regulation of MHC-Ⅰ and Ⅱ [21,26] . In this study, results also demonstrated the down-regulation of CD83, CD1a and HLA-DR molecules on MoDCs in CMV reactivated compared to non-reactivated liver transplanted patients.…”
Section: Discussionmentioning
confidence: 99%